2015
DOI: 10.5897/ajar2014.9010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Copper (Cu) application on soil available nutrients and uptake

Abstract: Effects of annual spraying of copper (Cu) fungicide by cocoa farmers in Nigeria needs immediate investigation to avoid copper toxicity which will affect uptake of other essential nutrients for plant growth. Laboratory and Screenhouse studies were carried out to investigate the effects of Cu application on availability of P, Zn, Fe and growth of maize. In the laboratory, copper was applied as CuSO 4 at 0, 10, 20, 30, 40 and 50 mg Cu kg-1 to 100 g soil and left for 5 weeks for equilibration while in the Screenho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…The results align with the earlier reports that plants grown in alluvial soils of Uttar Pradesh respond to Cu application even if the soil is not deficient in available Cu (Mehrotra, 1993; Ratan Kumar et al, 2009;Scheiber et al, 2013). Reduced grain yield in low Cu plants is in accordance with the reports of Mateos-Naranjo et al, (2008) and Azeez et al, (2015). This is due to the reduction in the number of effective tillers, disturbed setting of grains and the production of rudimentary and blind panicles in such plants.…”
Section: Grain Yield Attributes and Straw Yieldsupporting
confidence: 90%
See 1 more Smart Citation
“…The results align with the earlier reports that plants grown in alluvial soils of Uttar Pradesh respond to Cu application even if the soil is not deficient in available Cu (Mehrotra, 1993; Ratan Kumar et al, 2009;Scheiber et al, 2013). Reduced grain yield in low Cu plants is in accordance with the reports of Mateos-Naranjo et al, (2008) and Azeez et al, (2015). This is due to the reduction in the number of effective tillers, disturbed setting of grains and the production of rudimentary and blind panicles in such plants.…”
Section: Grain Yield Attributes and Straw Yieldsupporting
confidence: 90%
“…Previous results have also revealed that the excess Cu has very routinely accredited to an obtrusion with Fe metabolism. Ouzounidou (1994) and Azeez et al, (2015) reported that excess heavy metals may interrupt normal Fe metabolism and thus obvious to induce physiological Fe deficiency. However, Fe content in grain and straw at harvest stage with respect to different Cu levels increased up to 1.5 kg Cu ha -1 and decreased significantly with higher Cu level (2.5 and 3.0 kg ha -1 ).…”
Section: Tissue Concentrations Of Cu Mn Fe and Znmentioning
confidence: 99%
“…As for the average nutrients, all of them were significantly superior to the mean of the comparison treatment, as the highest value was for the treatment of Fe+Zn+Mn, which amounted to 149.31 Mg.h -1 , with an increase of 103.48% over the comparison average, while the lowest value was for the Zn+Cu treatment, which amounted to 92.26 Mg.h -1 , with an increase of 25.73% over the comparison average. It is noted from these results and from the table that the lowest values were for the treatments containing copper and for both methods of addition, especially those containing copper, zinc and manganese, one or both of them, which indicates the existence of an antagonistic relationship between the nutrients mentioned in addition to the negative role of copper in its effect on the readiness of phosphorus, zinc and iron in the soil Consequently, its absorbed by the plan and this turn leads to a decrease in productivity compared to other treatments, as mentioned by [31], and the positive effect of adding mineral micronutrients, whether sprayed on the vegetation or in addition with irrigation water, to increase the production of different crops has been shown by many researchers among them [32]. [33] and [34] who explained that although the addition of macronutrients in a way that fills the needs of the plant, in many researches these additions did not have a significant effect on increasing the production of the targeted agricultural crops due to the lack of available micronutrients, including mineral ones, in the soil, which It negatively affects the plant's need for these micronutrients, which is reflected in the failure to achieve the expected increase in production from the addition of macronutrients.…”
Section: Cumulative Total Yieldmentioning
confidence: 76%
“…The accumulation of ions such as Na + and Cl − accumulated in plant organs may compete with mineral nutrients and also disturb their uptake, translocation, and assimilation (Keutgen and Pawelzik, 2008). Higher concentrations of Cu reduced the content of N, P, and K in both shoot and root of maize; however, increased therein the concentration of Fe (Ali et al, 2002;Azeez et al, 2015). In sand culture grown cauliflower, the supply of 0.5 mM Cu for 30 days decreased Fe concentration (Chatterjee and Chatterjee, 2000).…”
Section: Nutrient-use-efficiency Of Plantsmentioning
confidence: 99%